The Emerald handbook of modern information management - Matarazzo, James M., 1941-; Pearlstein, Toby (Emerald Publishing Limited, 2017)
Award-winning information theorists and practitioners Pearlstein and Matarazzo have assembled a group of top international authors with experience in public, academic, government, and special library settings, including experienced independent information professionals, to address the critical issues facing Information Management (IM) today. This new handbook provides a context for approaching the world in which information professionals work; a tool, the Balanced Scorecard, to help demonstrate contribution and value; and a review of opportunities for new areas of employment and career development, ripe for applying the Information Services skill set. Through combinations of topical chapters with common themes, the professor and student will find a multi-perspective approach to the IM landscape. Used as a ready-reference, the IM practitioner will find both theoretical and pragmatic approaches to inform their decision making on traditional as well as new challenges. For information and IM professionals, librarians, and students, this must-have handbook provides invaluable insights from the leading names in the field, enabling you to make the best decision no matter what challenges you face.- Resumé vydavatel
Obsahuje index.
Keywords: informační management; informační věda; knihovnictví; information management; information science; librarianship; příručky; sborníky; elektronické knihy; handbooks and manuals; papers of several authors; electronic books